Penguatan Kompetensi Pegadogik Guru dalam Menyusun Pembelajaran Berdiferensiasi bagi MGMP Sejarah SMA Provinsi Jawa Tengah - Pramono, Suwito Eko; Amin, Syaiful; Utama, Nanda Julian; Lusianto, Junaidi Fery; Khotimah, Siti Khusnul; Riyanto, Muhammad Bagas; Prayoga, Teguh Irawan (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2024)
This study highlights the importance of differentiated learning in the context of Generation Z who have unique characteristics, such as critical thinking, desire for quick feedback, and technology literacy. Differentiated learning aims to meet individual learning needs by modifying four main components: content, process, product, and learning environment. Analysis of history teachers in Central Java Province shows that although most teachers have implemented some aspects of differentiated learning, there are obstacles in relevant and effective evaluation and assessment. To address this, a training program has been implemented to improve teacher competency in developing adaptive assessments, both formative and summative. The results of the training showed an increase in teachers' understanding and skills in implementing the principles of differentiated learning that are more inclusive and equitable.